Relationship between Obesity and Dental Caries in Saudi Male Adolescents. (8th October 2020) - Al-Ansari, Asim; Nazir, Muhammad
Abstract : Introduction . Obesity and dental caries are global public health problems. There are conflicting reports about the relationship between caries and obesity. Therefore, the study aimed to investigate the association between obesity and dental caries among male adolescents. Materials and Methods . This cross-sectional study included a sample of 258 male students' aged 12 to 15 years from schools in Dammam/Al-Khobar, Saudi Arabia. The study involved measuring caries prevalence and DMFT estimates, assessing body mass index (BMI), and administering a self-completion questionnaire. Independent samples Student's t- test, one-way ANOVA test, Pearson's correlation test, and bivariate and multivariate logistic regression analyses were performed. Results . Caries prevalence of the sample was 79.8%, and the mean score of DMFT was 3.55 ± 2.94. The mean BMI of participants was 23.42 ± 6.82 and 18% were obese (BMI > 30). The obese participants had a higher mean DMFT score (4.46 ± 3.54) than nonobese participants (3.35 ± 2.77) (P = 0.021 ). Similarly, the mean untreated caries was higher in obese (4.17 ± 3.22) than in nonobese participants (3.01 ± 2.66) (P = 0.010 ). In the logistic regression analysis, after controlling for father's education, family history of obesity, meals per day, fast food per week, and physical activity in the final model, the participants with high caries experience (DMFT = 5–15) were 2.21 times more likely to have obesity than those with low caries experience (DMFT = 0–4) (P = 0.04 ). No/school education of father (odds ratio 3.54, P = 0.011 ), family history of obesity (odds ratio 3.27, P = 0.002 ), and not performing physical activity (odds ratio 4.37, P = 0.002 ) were significantly associated with an increased likelihood of obesity. Conclusion . The prevalence of caries and obesity was high in male adolescents in Saudi Arabia. Obesity was significantly associated with untreated caries and caries experience. Children with high caries experience were more likely to have obesity than children with low caries experience. Preventive programs and policies should address public health issues related to caries and obesity in male teenagers.